Pembelajaran Pragmatik yang Terlupakan di Sekolah Dasar - Yohanna Claudia Dhian Ariani Harbelubun (Prosiding Temu Ilmiah Nasional Guru, 2022)
Elementary school students are also affected by the technology and IT development craze. The influence of gadget use among elementary students has grown because to the COVID-19 pandemic. This is incorrect since the world is changing quickly and we need to be ready to adapt if we don't want to fall behind. Ethics and communication guidelines must still be observed, despite the openness of communication venues. Elementary school pupils absolutely must learn about ethical communication. Of course, the school community, families, and the neighborhood community are involved in this. This article explores ideas regarding the value of pragmatic education beginning with elementary school students. This research methodology combines literature analysis and narrative inquiry. This article explores the revival of pragmatic education as a means of reinforcing communication ethics in young learners.